Seismic Performance Study of Multi-storey Building Structures with Nonlinear Time History Analysis Method - Eka Faisal Nurhidayatullah; Danang Ardiyanto (Universitas Medan Area, 2025)
Assessment of the structure of existing buildings is necessary, especially for multi-story buildings in risk category IV located in high seismicity areas such as Yogyakarta. If there are indications of weaknesses, immediate actions such as retrofitting and rehabilitation can be taken as disaster mitigation efforts. This study examines the seismic behavior and performance of buildings using the Nonlinear Time History Analysis method with modified real earthquake recordings through spectral matching processes to meet the target spectra. Deaggregation analysis shows that fault mechanism earthquakes with a magnitude range of 6.6-6.8 and a distance of 30-40 km are the most dangerous and potentially occurring. The selection of earthquake recordings based on deaggregation analysis results in five identical ground motions: Kobe, Imperial Valley, Friuli, and Northridge. Nonlinear time history analysis using these five ground motions, after spectral matching, shows that the largest base shear force and displacement along the x-axis of the building are influenced by the Imperial Valley earthquake, while along the y-axis by the Kobe earthquake. The performance of the structure against the Imperial Valley earthquake along the x-axis is at the Damage Control level, while the Kobe earthquake along the y-axis is at the Immediate Occupancy level. Plastic hinge analysis results indicate that most structural elements remain in good condition, with only a small potential for damage in the range of 2-5%. Shear walls have effectively functioned as energy dissipators, preventing damage to other structural elements, especially columns, and preventing the soft story effect. The Strong Column Weak Beam damage hierarchy pattern has been successfully achieved.